Detection of Surface Displacement of Mentawai Earthquake Mw7.8, October 25, 2010, using High Rate (HR) 1Hz GNSS Data. Issue 1 (1st January 2023) - Hardy, Thomas; Susilo,; Meilano, Irwan; Abidin, Hasanuddin Z; Rohadi, Supriyanto; Sudrajat, Ajat; Retno Agung, K; Manurung, Alpon Sepriando; Susilanto, Pupung; Karnawati, Dwikorita
Abstract: Conventional seismic sensors, may have some problems, for example, seismometers are vulnerable to clipping and going off-scale when recording in the near-field of large earthquakes, that caused magnitude saturation. High-rate GNSS measurement can avoid the problems in conventional seismic records, in determining true size of large earthquake. The Mw7.8 Mentawai earthquake on October 25, 2010, generate significant tsunami run-up reached 9.3 m, five hundred more casualties, and raise economic loss of 200 bilions rupiahs. We utilize 1 Hz high-rate GNSS data from 11 GNSS stations of the Sumatran GPS Array (SuGAr) network operated by Earth Observatory of Singapore (EOS) associated with the October 25, 2010, Mw7.8 Mentawai earthquake. We generate displacement waveform in three components (east, north, up) and it can be seen that all GNSS stations can detect surface displacement caused by October 25, 2010, Mw7.8 Mentawai earthquake. We also display the displacement waveform based on the distance from the GNSS station to the earthquake hypocenter, and found that displacement amplitude decreases as the distance between the earthquake hypocenter and the location of the GNSS station increases.